2022
DOI: 10.2147/jir.s365545
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Histone Deacetylase 4 is Associated with Aging Cartilage Degeneration and Chondrocyte Hypertrophy

Abstract: Purpose To determine the role of histone deacetylase 4 (HDAC4)-controlled chondrocyte hypertrophy in the onset and development of age-related osteoarthritis (OA). Methods Morphological analysis of human knee cartilages was performed to observe structural changes during cartilage degeneration. HDAC4 expression was deleted in adult aggrecan (Acan)-CreERT2; HDAC4fl/fl transgenic mice. The onset and development of age-related OA were investigated in transgenic and control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Sox-9driven transactivation is epigenetically controlled by several enzymes: histone acetyltransferases, methyltransferases ESET and EZH2, and the demethylase Phf2 [42][43][44]. HDAC4, a NAD+-independent histone deacetylase, triggers Sox-9 and the hypertrophic transition, as observed by Dong Z. et al in a longitudinal study of ACAN-CreERT2-HDA4 fl/fl transgenic mice with early, age-related OA with synovitis and osteophyte formation; HDAC4 silencing resulted in a very significant increase in RunX2, Col10a1, IHH signaling and MMP-13 expression, whereas Sox-9, ACAN and Col2a1 were overtly suppressed [45]. SIRT1 and SIRT6 exert important downstream regulation: the former increases COL2A1 and ACAN expression in the healthy state, while the latter suppresses several inflammatory genes.…”
Section: Sox-9 Nf-kb and Proinflammatory Cytokines Mediate Hypertroph...mentioning
confidence: 61%
“…Sox-9driven transactivation is epigenetically controlled by several enzymes: histone acetyltransferases, methyltransferases ESET and EZH2, and the demethylase Phf2 [42][43][44]. HDAC4, a NAD+-independent histone deacetylase, triggers Sox-9 and the hypertrophic transition, as observed by Dong Z. et al in a longitudinal study of ACAN-CreERT2-HDA4 fl/fl transgenic mice with early, age-related OA with synovitis and osteophyte formation; HDAC4 silencing resulted in a very significant increase in RunX2, Col10a1, IHH signaling and MMP-13 expression, whereas Sox-9, ACAN and Col2a1 were overtly suppressed [45]. SIRT1 and SIRT6 exert important downstream regulation: the former increases COL2A1 and ACAN expression in the healthy state, while the latter suppresses several inflammatory genes.…”
Section: Sox-9 Nf-kb and Proinflammatory Cytokines Mediate Hypertroph...mentioning
confidence: 61%
“…Studies in recent years have suggested that HDAC4 exerts a regulatory function in endplate chondrocyte degeneration and NP cell degeneration [32]. For instance, HDAC4 bolsters morphological alterations in endplate chondrocytes and augments ECM degradation and endplate cartilage degeneration [33].…”
Section: Discussionmentioning
confidence: 99%
“…The role of IHH in cartilage biology is better researched as it is involved in chondrocyte hypertrophy during development [ 82 ]. Studies have shown that the IHH signalling is dysregulated in OA and IHH expression is elevated in OA cartilage to promote hypertrophy, apoptosis and senescence [ 83 , 84 , 85 ]. In another study, inhibition of IHH signalling by ipriflavone, a compound that inhibits the IHH pathway, led to increased chondrocyte proliferation and reduced apoptosis and cartilage degeneration [ 53 ].…”
Section: Discussionmentioning
confidence: 99%